ANALYSIS OF NEW PRODUCT DEVELOPMENT BY USING QUALITY FUNCTION DEPLOYMENT (QFD): A STUDY OF KOMBUCHA - Noel Bentara Immanuel; Adi Saptari; Dedi Kurniawan; Isa Halim (President University, 2021)
Competitiveness of product innovation depends on how the company can answer the customers’ needs. To capture the right needs, product designer has to go and ask the customers and summary them into priority and translate the needs into technical requirement in order to produce the competitive product. At this era there are many kinds of drinks available in the market. Tea is one of the popular drinks for quite long. Different types of flavor tea created to find its market. This study is trying to offer a new product of Kombucha tea, a fermented tea. A method of Quality Function Deployment (QFD) was implemented to come out the right design of Kombucha tea which may absorb the customer needs. This was done through the questionaries and interview to the community. Based on this information then provide some technical requirements to produce the right quality Kombucha tea that are wanted by the customer. The results show customer requirement from the questionnaires 59% of respondents agrees that they buy Kombucha due to its taste. While 82% respondent agree on the Fuzzy sensation of kombucha taste. Packaging (Appearance), 58% like the package. And for Health benefit, respondents 83% agree. For easiness to get, respondents only gave 31%. The customer need should be transformed into Functional or technical measures. The study analyzed that there are 13 Functional aspects determined the end quality of Kombucha tea. This study presented on how to translate the customer needs into functional requirements to produce the right product.Keywords: QFD, kombucha, product development, customer needs